2016
DOI: 10.1162/evco_a_00181
|View full text |Cite
|
Sign up to set email alerts
|

Solving Multiple Isolated, Interleaved, and Blended Tasks through Modular Neuroevolution

Abstract: Many challenging sequential decision-making problems require agents to master multiple tasks. For instance, game agents may need to gather resources, attack opponents, and defend against attacks. Learning algorithms can thus benefit from having separate policies for these tasks, and from knowing when each one is appropriate. How well this approach works depends on how tightly coupled the tasks are. Three cases are identified: Isolated tasks have distinct semantics and do not interact, interleaved tasks have di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…We also demonstrated that evolution guided towards a single user-defined decomposition does not perform well for tasks that do not have a very obvious structure. This agrees with previous work demonstrating that evolving neural networks often end up with unexpected decomposition patterns not agreeing with human intuition (Huizinga et al, 2016;Schrum and Miikkulainen, 2016b;Ellefsen et al, 2015). The technique of guiding evolving neural networks towards a diversity of decomposition patterns presents a way to take advantage of unexpected, creative solutionsallowing an automatic way to discover many functional problem decompositions.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We also demonstrated that evolution guided towards a single user-defined decomposition does not perform well for tasks that do not have a very obvious structure. This agrees with previous work demonstrating that evolving neural networks often end up with unexpected decomposition patterns not agreeing with human intuition (Huizinga et al, 2016;Schrum and Miikkulainen, 2016b;Ellefsen et al, 2015). The technique of guiding evolving neural networks towards a diversity of decomposition patterns presents a way to take advantage of unexpected, creative solutionsallowing an automatic way to discover many functional problem decompositions.…”
Section: Resultssupporting
confidence: 88%
“…Modularity in evolving neural networks has been demonstrated to improve performance on complex tasks, as it allows problem decomposition, hierarchical knowledge structures and multimodal behavior. There is therefore a growing interest in techniques for increasing the functional modularity of evolving neural networks (Clune et al, 2013;Mengistu and Clune, 2016;Schrum and Miikkulainen, 2016b;Velez and Clune, 2017). Most techniques for increasing modularity in neuroevolution belong to one of two extremes.…”
Section: Introductionmentioning
confidence: 99%
“…21,23-25 In contrast, artificial intelligence tools for structured data are available and have already surpassed human performance in many areas. 25-31 Of note, bioinformatics pipelines generate mostly structured, discrete data. Thus, we consider the inability of humans to gain access to the full potential of the pipeline output, coupled with the discrete nature of the data and the final binary reporting decision, as an ideal setting 32 to assess the performance of an artificial intelligence–based decision support system for variant reporting.…”
Section: Introductionmentioning
confidence: 99%
“…However, after activating certain power-ups, the ghosts become vulnerable for a brief period of time. The agent can consume these ghosts for a score boost.The switch in ghost dynamics necessitates a change in the game-play strategy, since multiple distinct modes of behavior are required under different conditions [4,5]. Despite the need for multi-modal behaviors, conventional reinforcement-learning approaches have focused on constructing monolithic policies.…”
mentioning
confidence: 99%